Post-abortion contraceptive acceptance and choice among women receiving abortion care at Saint Paul's Hospital, Addis Ababa, Ethiopia: a cross-sectional study - Matiyas Asrat; Delayehu Bekele; Sarah D Rominski (Elsevier, 2018)
Background: An exploration and comparison of the characteristics and choices of women who did and did not accept post-abortion contraception would help to provide recommendations for more effective and appropriate contraceptive counselling and services. We aimed to determine the contraceptive acceptance rate and factors associated with choice of contraception, in particular modern and long-acting methods, in women after an abortion at a hospital in Addis Ababa, Ethiopia. Methods: We did a cross-sectional study at Saint Paul's Hospital Millennium Medical College, Addis Ababa, Ethiopia, with women who received abortion care services for induced or spontaneous abortions from January to June, 2015. Logistic regression was used to determine factors associated with acceptance and choice of method of contraceptives. Findings: 552 women were included in the study. 478 had spontaneous abortions and 74 had induced abortions. 500 (91%) of them adopted modern contraception post-abortion and 103 (19%) received long-acting reversible contraceptives (LARC). Multivariable analysis showed that being a housewife (adjusted odds ratio [aOR] 3·43, 95% CI 1·20-9·80), being married (3·31, 1·41-7·74), and parity greater than 1 (2·70, 1·04-7·03) had a significant association with the odds of adopting any modern method of contraception after abortion. Adoption of LARC was positively associated with being a student (4·62, 1·50-14·22), parity greater than 1 (2·21, 1·12-4·36), and induced abortion (2·91, 1·46-5·80). Interpretation: The post-abortion contraceptive acceptance rate was higher than other studies done in Ethiopia. However, there should be increased advocacy and multipronged activities by the hospital and federal Ministry of Health to further increase the acceptance of LARC post abortion. Further research to assess follow-up discontinuation rates of contraceptive methods after discharge is an important next step. Funding: Saint Paul's Hospital Millennium Medical College.